2014
DOI: 10.1088/0256-307x/31/4/047401
|View full text |Cite
|
Sign up to set email alerts
|

Critical-Current Degeneration Dependence on Axial Strain of Bi-based Superconducting Multi-filamentary Composite Tapes

Abstract: Superconducting materials are always severely restricted in practical engineering applications due to their carryingcurrent degradation under mechanical loads. Based on Ekin's exponential model and Weibull's distribution function, we propose an empirical degradation model for describing the mechanical deformation influence on the critical-current of Bi-based superconducting multi-filamentary composite tapes under axial loading. The critical currents of superconducting tapes depending on the axial strain are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…Furthermore, irreversible degradation of I c in both BSCCO-based (e.g. Bi-2212 and Bi-2223) and REBCO conductors has been studied using a statistical approach based upon the Weibull statistics [31,32,[42][43][44][45]. Here a critical current phenomenological model that combines the Ekin power-law formula and the Weibull distribution function with the REBCO conductor model is used to predict the electromechanical behavior of I c in REBCO conductors across the entire strain range.…”
Section: Uniaxial Tensile Load Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, irreversible degradation of I c in both BSCCO-based (e.g. Bi-2212 and Bi-2223) and REBCO conductors has been studied using a statistical approach based upon the Weibull statistics [31,32,[42][43][44][45]. Here a critical current phenomenological model that combines the Ekin power-law formula and the Weibull distribution function with the REBCO conductor model is used to predict the electromechanical behavior of I c in REBCO conductors across the entire strain range.…”
Section: Uniaxial Tensile Load Simulationmentioning
confidence: 99%
“…Ignoring the linear deformation effect on the REBCO cross-section area, and assuming a uniform distribution of current on the REBCO layer, the normalized critical current A statistical approach based upon the Weibull distribution function has been used to characterize the effective area of undamaged superconducting region under deformation in BSCCO-based conductors [42][43][44][45], and the irreversible degradation of I c in both BSCCO-based and REBCO conductors [31,32]. The statistical ratio of undamaged superconducting cross-section area to the before-damaged superconducting cross-section area under uniaxial loadings, S S , Figure 13 compares the simulation result calculated by (24) against the experimental data taken from [8] for the applied strain dependence of (normalized) critical current.…”
Section: Uniaxial Tensile Load Simulationmentioning
confidence: 99%
“…The shape parameters c and t of Weibull's distribution function are usually constrained less than 6 [21]. In our study, they are assumed to be equal each other for simplicity, that is, c = t = 2, which gives good predictions coincident with experiment data for Bi-based superconductor composite tape under both tension and compression states [25]. The scaling parameters of Weibull's distribution function e c , e t are the fitting parameters based on tensional and compressive tests.…”
Section: Model Application and Discussionmentioning
confidence: 87%
“…For a bent Bi2223-composite tape, ideally, one side of the neutral axis is stretched, and the other side is compressed. From the view of damage of fiber-reinforced composites, the ratio of the number of undamaged superconducting filaments to the total number of superconducting filaments under tension and compression conditions satisfies Weibull distribution, as follows [22][23][24][25]:…”
Section: Basic Equationsmentioning
confidence: 99%
“…Then, Gao et al combined the damage evolution model [33] with the Weibull-type damage distribution [34] and reproduced I L c (ε app ) measured by bending dies and changes in I L c and I UL c during loading-unloading cycles [35]. Gao et al also reported a model that involves the uniaxial strain dependence of J c and the Weibull-type damage evolution [36].…”
Section: Discussion On Gradual εApp-linear Ic Decrease In Reversible ...mentioning
confidence: 99%